An impact of age, birth order and qualification on women in sports participation levels in Tamilnadu and Pondicherry - Muthu, A; Jayanthi, V; Sakthigananavel, D (Journal of Experimental Sciences, 2011)
The position, a child had by the order of birth significantly affected the child’s growth and personality. Research in the late twentieth century and early twenty-first century shows even greater influence, contributing to intelligence, career choice, and to a certain degree, success in adulthood. Until the independence of India, The present research is to examine whether the age, order of birth and qualification of women have any impact on women's participation in sports among Tamil Nadu and Pondicherry at different levels. Sixty women players were randomly selected from 4 Colleges of two different states. First half from Cuddalore, Tamil Nadu state and second half from Karaikal, Pondicherry state. The selected subjects were with a brief questionnaire, to find out their level of sports participation, age, order of birth and qualification. Data obtained were subjected to find out statistical significance among the means using 3 (levels - district, state and national participations) x 2 (states -Tamil Nadu and Pondicherry) Factorial analysis. The results proved that there were significant differences in age and qualifications of the different level of women players. There was no significant difference among the states, Tamil Nadu and Pondicherry in age, order of birth and qualifications of the women players. It was concluded that age and qualification play vital role in the participation level of women players.